2016
DOI: 10.1111/nph.13895
|View full text |Cite
|
Sign up to set email alerts
|

An interdomain network: the endobacterium of a mycorrhizal fungus promotes antioxidative responses in both fungal and plant hosts

Abstract: SummaryArbuscular mycorrhizal fungi (AMF) are obligate plant biotrophs that may contain endobacteria in their cytoplasm. Genome sequencing of Candidatus Glomeribacter gigasporarum revealed a reduced genome and dependence on the fungal host.RNA-seq analysis of the AMF Gigaspora margarita in the presence and absence of the endobacterium indicated that endobacteria have an important role in the fungal pre-symbiotic phase by enhancing fungal bioenergetic capacity. To improve the understanding of fungalendobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 67 publications
2
70
0
Order By: Relevance
“…Taking in account the results discussed above, we argued that CaGg may have a protective effect on G. margarita, making the fungal host more efficient in detoxifying endogenous ROS. Consistent with this, proteomic data confirmed that the B-spores produced less thioredoxin and other ROS-detoxifying proteins, and showed signs of oxidative damage (Vannini et al 2016).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…Taking in account the results discussed above, we argued that CaGg may have a protective effect on G. margarita, making the fungal host more efficient in detoxifying endogenous ROS. Consistent with this, proteomic data confirmed that the B-spores produced less thioredoxin and other ROS-detoxifying proteins, and showed signs of oxidative damage (Vannini et al 2016).…”
Section: Introductionsupporting
confidence: 71%
“…This result may be explained by considering that the expression of these ROS scavengers is already higher in the B+ control fungus, when compared to the B-control (B+ control vs B-control comparison). A similar expression pattern has already been described for glutathione S-transferase and peroxiredoxin, which were shown to be specifically up-regulated at transcript and protein levels in the B+ line under normal growth conditions Vannini et al 2016). Thus, given that G. margarita B+ efficiently elicits the ROS scavengers, it potentially needs a lower activation of these genes when compared to the less-efficient B-line upon H2O2 treatment.…”
Section: Hydrogen Peroxide Treatment: Identification Of the Main Genementioning
confidence: 68%
See 3 more Smart Citations